Organic Fertilizers - From Basic Concepts to Applied Outcomes 2016
DOI: 10.5772/62325
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic Fertilizers on Phenolic Profiles and Fatty Acids Composition: A Case Study for Cichorium intybus L.

Abstract: Radicchio (Cichorium intybus L.) is an increasingly appreciated leafy vegetable that exhibits great diversity in appearance, including different colored leaves, rosettes, or heads. Varieties of radicchio ('Treviso', 'Verona' 'Anivip', 'Castelfranco', and 'Monivip') commonly produced in Slovenia were investigated for their phenolic and fatty acid profiles. Plants were grown under organic and/or mineral fertilizer managements in greenhouse conditions. High-performance liquid chromatography analysis was used to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…On the contrary, the lowest total fatty acids resulted from the application of biofertilisers alone either in first or second season in comparison to control and all other treatments. Our previous data are in conformity with the results obtained by Sinkovič and Žnidarčič (2016) on Radicchio plant. The different influences of humic substances, nano zeolite and biofertilisers mixed (HNB) on total phenolics, total flavonoids and total fatty acids and physiological activities could be due to the power of releasing and chelating available nutrients for plant uptake along with their impacts on physiochemical and biological properties, which also enable efficient use of biofertilisers and organic fertilisers.…”
Section: Effect On Total Phenolics Total Flavonoids and Total Fatty supporting
confidence: 93%
“…On the contrary, the lowest total fatty acids resulted from the application of biofertilisers alone either in first or second season in comparison to control and all other treatments. Our previous data are in conformity with the results obtained by Sinkovič and Žnidarčič (2016) on Radicchio plant. The different influences of humic substances, nano zeolite and biofertilisers mixed (HNB) on total phenolics, total flavonoids and total fatty acids and physiological activities could be due to the power of releasing and chelating available nutrients for plant uptake along with their impacts on physiochemical and biological properties, which also enable efficient use of biofertilisers and organic fertilisers.…”
Section: Effect On Total Phenolics Total Flavonoids and Total Fatty supporting
confidence: 93%
“…Additionally, in our previous study we showed that compared to the red cultivars, 'Castelfranco' treated with Organic+Mineral fertiliser had considerably lower levels of hydroxycinnamic acids, flavonols and other unknown phenolic compounds [14,15]. D'Evoli et al [26] compared 'Treviso' and 'Castelfranco' chicory plants, and showed that anthocyanin contents are much higher for 'Treviso' compared to 'Castelfranco' (13-45 vs. 4-6 mg/ 100 g FW, respectively).…”
Section: Discussionmentioning
confidence: 92%
“…2 and 3; Additional file 2: Table S2 Additional file 3: Table S3). The reasoning followed was that the application of different fertilisers can influence the general chemical composition of chicory plants, which will including their production of secondary metabolites, such as TPCs and TFCs, as stress responses [14,15,28], which will then result in different antioxidative activities. For the red cultivars, compared to the Control, Orga-nic+Mineral fertiliser treatment resulted in higher TPCs (except for cultivar 'Verona') and TFCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations